Informatics - ., . (Journal of Engineering Education Transformations, 1997)
The Textile Machinery Manufacturers Association (TMMA) India recently signed an MoU with IIT Mumbai to establish the D. K. Devarajuly Chair Professorship and five student fellowships in Textile Engineering at lIT Mumbai. TMMA handed over a cheque for Rs. 5 lacks on this occasion as endowment for this purpose.